ҚАРАҚАЛПАҚ ҲӘМ ҚАЗАҚ ШАЙЫРЛАРЫ АЙТЫСЛАРЫНЫҢ ТЕКСТОЛОГИЯСЫ МӘСЕЛЕСИ - Давлетов, Б.А. (FAN va JAMIYAT, 2021)
This article provides a comparative analysis of the testology of sayings of Karakalpak poets and Kazakh poets. The texts of the poet Kulimbet’s letter to Abubakir Kerderi have been studied. It is scientifically explained that the texts are presented in different variants in different texts.